Complete plastome sequence of Ilex asprella (Hooker and Arnott) Champion ex Bentham (Aquifoliaceae), a Chinese folk herbal medicine. Issue 2 (3rd July 2019) - Chen, Yan; Chen, Hua-Xu; Li, Hai-Li; Cheng, Xia-Lan; Wang, Li-Yun
Abstract: The complete chloroplast genome of Ilex asprella, a species of Aquifoliaceae is reported for the first time in this study. The complete chloroplast genome of I. asprella is 157, 856 bp in length with a typical quadripartite structure, consisting of a large single-copy region (LSC, 87, 258 bp), a single-copy region (SSC, 18, 441 bp) and a pair of inverted repeats (IRs, 26, 082 bp). There are 114 genes annotated, including 85 unique protein-coding genes, four unique ribosomal RNA genes, and 30 transfer RNA genes. To investigate the evolution status of T. concolor, as well as Scrophulariaceae, we build a phylogenetic tree with I. asprella and other eight species based on their complete chloroplast genomes. According to the phylogenetic topologies, I. asprella was closely related to I. wilsonii .